2019
DOI: 10.1097/shk.0000000000001198
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Dynamics of Stem and Progenitor Cells in Blood of Polytraumatized Patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
1
0
2
Order By: Relevance
“…A nadir of HSPCs in PB was also observed in polytrauma (PT) patients, although at 24 h post-PT. The overall dynamics of the frequency of SPCs in mice upon TXT is therefore somewhat similar to the inverse bell-shaped pattern of the frequency of HSCPs in PB of polytrauma patients that was recently described by us (23), but with an accelerated change in mice.…”
Section: Resultssupporting
confidence: 84%
“…A nadir of HSPCs in PB was also observed in polytrauma (PT) patients, although at 24 h post-PT. The overall dynamics of the frequency of SPCs in mice upon TXT is therefore somewhat similar to the inverse bell-shaped pattern of the frequency of HSCPs in PB of polytrauma patients that was recently described by us (23), but with an accelerated change in mice.…”
Section: Resultssupporting
confidence: 84%
“…AMPC were isolated and cultured from human PB, which is a heterogeneous pool of cells with several cell types that show some stem markers of HSPCs/MNCs, MSCs, EPCs, and VSELs. We suggest 2 major reasons for the difference in expression between AMPC and other HSPCs/MNCs, MSCs, EPCs, HSCs, [ 24 , 25 ] and VSELs [ 5 , 10 , 26 , 27 ] stem cells, including the addition of growth factors for culture and granulocyte colony-stimulating factor treatment for enriched stem cell collection for other stem cells, [ 5 , 28 ] but not for AMPC. Our results indicated that CD29 and CD44 achieved 90% to 100% expression ratios in AMPC (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Essa interação é bidirecional, de modo que a inflamação não apenas leva à ativação da coagulação, como também ativa as proteases de coagulação, que regulam de forma direta e indireta a inflamação. Em alguns casos, como na infecção grave ou sepse, a ativação sistêmica da inflamação e coagulação podem se manifestar de forma órgão-específica, o que pode ser relevante para a disfunção orgânica subsequente (VOLPIN et al, 2014;GUISASOLA et al, 2018;VOGEL et al, 2019).…”
Section: Revisãounclassified
“…Se não for adequadamente neutralizada pela fibrinólise, a deposição de fibrina pode causar obstrução difusa da microvasculatura. Além disso, a expressão de VOGEL et al, 2019). Existe a correlação da resposta de IL-6 e IL-10 no trauma com gravidade e mortalidade da lesão, nas primeiras 24 horas além disso outros estudos também mostraram o papel da IL-6 no diagnóstico precoce de complicações pós-trauma (OSUKA et al, 2014;DEKKER;KRIJNEN;SCHIPPER, 2016;NAMAS et al, 2015;KHURANA et al, 2019).…”
Section: Revisãounclassified